Investigating the impact of institutional forces on the operations of an organisation-implemented ERP system in a developing country - Bitsini, Nkosinathi (Department of Information Systems, 2017)
In response to the pressure of the ever-changing and dynamic global market, enterprise resource planning (ERP) systems have become the cornerstone for organisations of all sizes to compete internationally. However, implementing organisations in developing countries doesn't enjoy the same benefits as implementing organisations from developed countries, because ERP systems general originate from developed countries and these do not necessarily fit the requirements of implementing organisations in developing countries owing to the different business practices, legal and government regulations. ERP systems are built on institutional models, procedures and forces that set the rules of rationale and these forces serve to bind implementing organisations to fundamental choices about how organisational operations and processes should be organised. Limited studies have been done on the impact of institutional forces on implementing organisations from developing countries, particularly in South Africa, yet these organisations continue to invest huge amounts of their financial resources in ERP systems. Until implementing organisations understand the impact of institutional forces on their operations, misalignment will continue to deny realisation of the full benefits of these systems. This study aimed at exploring the institutional forces and their impact on the operations of the implementing organisation within the South African context. A qualitative research approach was undertaken from an interpretive epistemological position. A single case study was conducted at Organisation X. Organisation X is a public sector organisation formed in 1999 and implemented an ERP system in 2006. Thirty employees participated in the study and the data were analysed using the thematic analysis qualitative technique. The selected participants only include those who joined the Organisation X before the implementation of the ERP system because they have a broad general knowledge of the ERP and have undergone the experience during this time. These include executive managers, senior managers and support staff. Major themes from the data illustrate that implementing organisations from the public sector resort to modifying the ERP because they operate in highly regulated environments. These themes also demonstrate that economic differences, sector requirements, organisational culture, IT infrastructure and operational differences are the institutional forces that affect the implementation and use of software packages. The findings reveal that ERP-embedded institutional forces have a negative impact on the implementing organisational structures, bring changes to the process controls and procedures of the implementing organisation, affect the reporting structure of the organisation, create additional roles and responsibilities, bring undesirable changes to organisational culture and increase organisational spending in IT infrastructure. Institutional forces also have positive impact on implementing organisation operations, including improved availability, accessibility, accuracy and reliability of the information and, lastly, thus improve the effectiveness and efficiency of operations. The findings of this study help to build a body of knowledge on ERP misalignment for organisations planning to implement or adopt ERP systems. This study alerts implementing organisations of the need to systemically review regulations and national rules together with industry best practices prior to deployment.